Financeirização para organização do trabalho : transformações na área de gestão de pessoas da Petrobras - Lima, Luana Duarte Ferrari Lopes (2019)
The process of financialization is a phenomenon arising from the evolution of capitalism that causes organizational and cultural changes. Financialization means the process of valuing financial capital within organizations, where the logic of the financial market emerges in business environments. The emergence of financialization alters management at work, making visible new flexible arrangements aimed at expanding results, optimizing costs and generating shareholder value. Thus, this research seeks to understand how financialization changes the organization of work in the area of People Management at Petrobras and causes changes to the organizational culture. For this, the participant observation, the archives and the questionnaire were the instruments that made up the methodological contribution of the case study. The results show that the area of People Management has been metamorphosing as Petrobras redefined its business priorities and the arrival of financialization brings new organizational changes and the herald of cultural transformation.